Peranan Intrinsic Value terhadap Motivasi Belajar pada Mahasiswa di Jabodetabek - Riana Sahrani; Hody Denilson; Willy Tasdin (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Education is the learning of knowledge, skills, and habits of a group of people that are passed down from one generation to the next through teaching, training, or research. Education often occurs under the guidance of others, but is also possible autodidactically. The etymology of the word Education comes from the Latin "Educare" which means "to educate" or to nurture, learning motivation is the desire that arises in students that causes learning activities to occur. The existence of learning motivation will ensure the sustainability of learning activities and provide direction to learning activities so that the goals desired by the learning subject can be achieved. And intrinsic value refers to the actual and fundamental value of a learning, and intrinsic value is used in learning in the formation of student values ​​in the ongoing learning process, in this study involved 306 student respondents from all over the Jabodetabek area with the value of the regression test measured into the coefficient b result of 0.286 for every 1% addition it will increase by 1,060 which is measured in the regression value equation Y = 0.286 - 1.060 and also the criteria for adding ha at 0.000 which means less than 0.05 which means there is no significance in the regression test properly.